Impact of tidewater glacier retreat on the fjord system: Modeling present and future circulation in Kongsfjorden, Svalbard. (1st May 2019) - Torsvik, Tomas; Albretsen, Jon; Sundfjord, Arild; Kohler, Jack; Sandvik, Anne Dagrun; Skarðhamar, Jofrid; Lindbäck, Katrin; Everett, Alistair
Abstract: Tidewater glaciers in Kongsfjorden, Svalbard, are retreating, and it is expected that they will terminate on land at some time in the future. Plumes, the submerged runoff emerging at the bases of tidewater glacier fronts, contribute to large-scale circulation within the inner fjord. A transition to a fjord with only land-terminating glaciers will affect the fjord circulation, with further implications for the biogeochemistry and ecosystem in Kongsfjorden. In this paper we compare the present and predicted future circulation using the ocean model system ROMS, and identify and quantify changes resulting from the altered forcing. Removal of subglacial discharge due to retreating tidewater glaciers causes substantial reduction of subsurface volume fluxes, and hence exchange rates, in the inner part of the fjord, and results in enhanced stratification during summer months. The increase in fjord extent due to tidewater glacier retreat results in a slight increase in tidal velocities, in particular overtide components, but this effect is not strong enough to compensate for the reduction in current velocities due to removal of freshwater plumes at glacier fronts. The freshwater content (practical salinity < 34.8 ) in the fjord during the melting season is predicted to increase in the future, primarily due to enhanced retention of freshwater in the inner parts of the fjord. However, freshwater in the future will mostly be confined to a relatively thin surface layer whereas at present freshwater is found in a thicker layer, in particular in the proximity of the tidewater glacier fronts.